Coupling morphometric analysis and soil erosion modeling for the characterization of the geomorphological setting in the surrounding of the archaeological site of Chimtou (Central Medjerda Valley, Tunisia) - Julia Pagels; Moheddine Chaouali; Corisande Fenwick; Philipp von Rummel; Wiebke Bebermeier (Journal of Maps)
This study focuses on the characterization of the geomorphological setting in the hinterland of the archaeological sites of Chimtou and Bordj Hellal located in the central Medjerda Valley, North Tunisia. Our approach integrates the algorithm Geomorphons for semi-automatic landform classification with the soil erosion model Unit Stream Power-based Erosion Deposition (USPED), providing information on the intensity and regional distribution of erosional and depositional processes. Data from geomorphological field mapping provide a database for a ground-truth of the semi-automatic landform classification derived by the algorithm Geomorphons and complemented the database for the creation of a detailed map of the geomorphology in the hinterland of Chimtou. In line with the delineation of the spatial distribution of erosional and depositional processes, the results deepen the understanding of the geomorphology and the sediment routing of this region.